2022
DOI: 10.3389/fneur.2022.854846
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biomarkers of Acute Ischemic Stroke Etiology Revealed by Mass Spectrometry-Based Proteomic Characterization of Formalin-Fixed Paraffin-Embedded Blood Clots

Abstract: Background and AimsBesides the crucial role in the treatment of acute ischemic stroke (AIS), mechanical thrombectomy represents a unique opportunity for researchers to study the retrieved clots, with the possibility of unveiling biological patterns linked to stroke pathophysiology and etiology. We aimed to develop a shotgun proteomic approach to study and compare the proteome of formalin-fixed paraffin-embedded (FFPE) cardioembolic and large artery atherosclerotic (LAA) clots.MethodsWe used 16 cardioembolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 91 publications
1
9
1
Order By: Relevance
“…Proteomics analysis by Rao et al further found that APOE levels were negatively related to erythrocyte sedimentation rate levels, suggesting greater inflammation associated with APOE expression 25. Protein levels of glycoprotein IX platelet (GP9), which was differentially expressed across all comparisons in our study (higher in CE), were also found to be greater in CE cases by a proteomics characterization by Rossi et al 28. Similarly, integrin subunit β3 (ITGB3), which was also differentially expressed across all comparisons (greater in CE) in our study was also found to higher in CE by Suissa et al 29 in their proteomic study.…”
Section: Discussionsupporting
confidence: 73%
“…Proteomics analysis by Rao et al further found that APOE levels were negatively related to erythrocyte sedimentation rate levels, suggesting greater inflammation associated with APOE expression 25. Protein levels of glycoprotein IX platelet (GP9), which was differentially expressed across all comparisons in our study (higher in CE), were also found to be greater in CE cases by a proteomics characterization by Rossi et al 28. Similarly, integrin subunit β3 (ITGB3), which was also differentially expressed across all comparisons (greater in CE) in our study was also found to higher in CE by Suissa et al 29 in their proteomic study.…”
Section: Discussionsupporting
confidence: 73%
“…Metabolomics combined with machine learning techniques used in this study may be a promising new approach for stroke etiology. Proteomics is also a promising technique to assess stroke etiology 13 14. Rossi et al found that proteins in the ubiquitin–proteasome pathway, blood coagulation or plasminogen activating cascade, cytoskeletal remodeling of platelets, platelet adhesion, or blood coagulation were different between the two types of thrombi 14.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics is also a promising technique to assess stroke etiology 13 14. Rossi et al found that proteins in the ubiquitin–proteasome pathway, blood coagulation or plasminogen activating cascade, cytoskeletal remodeling of platelets, platelet adhesion, or blood coagulation were different between the two types of thrombi 14. Proteomics indicates events that are occurring, whereas metabolomics closest to the phenotype of biological system reflect events that have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi et al used mass spectrometry to compare 16 CE vs. 15 LAA thrombi in AIS patients [ 35 ]. They found 14 DEPs among 1581 identified proteins.…”
Section: Multiomic Studiesmentioning
confidence: 99%